Defective Subviral Particles Modify Ecological Equilibria and Enhance Viral Coexistence - Lucia-Sanz, Adriana; Aguirre, Jacobo; Fraile, Aurora; García-Arenal, Fernando; Manrubia, Susanna (Frontiers in Virology, 2022)
Cooperation is a main driver of biological complexity at all levels. In the viral world, gene sharing among viral genomes, complementation between genomes or interactions within quasispecies are frequently observed. In this contribution, we explore the effects of flexible associations between fully fledged viruses and subviral entities, such as virus satellites, in viral dynamics and, in particular, in stable viral coexistence. We devise a mathematical model to compare different situations of competition between two viruses and to quantify how the association with a satellite qualitatively modifies dynamical equilibria. The relevant parameter is the invasion fitness of each virus or of the virus-satellite tandem, which in the model depends on the transmission rate of viruses and on their effect on host survival. In a virus-virus competition, one of the viruses becomes eventually extinct, recasting the competitive exclusion law of ecology. However, an association with a satellite might change the outcome of the competition in two ways, either to favor the less competitive virus (regardless of whether it is the helper virus or not) or to allow for the stable coexistence of the two viruses and the satellite. The virus-satellite association differs from other mechanisms proposed in ecology to date to enhance species coexistence. We hypothesize that such an association constitutes a parsimonious evolutionary pathway towards more stable cooperative associations, such as bipartite viral forms, a collaborative association unique to viruses.